2018
DOI: 10.1039/c8cy01346b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and evaluation of iron nanoparticles as hydrogenation catalysts in alcohols and tetraalkylphosphonium ionic liquids: do solvents matter?

Abstract: Best recyclability seen for Fe nanoparticles in alcohol solvents in which Fe-core, Fe oxide shell nanoparticles are formed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Studies by TEM and UV-Vis spectroscopy showed that nanoparticles can be regenerated and their activity recovered by reversing sintering [10]. The same group also showed that Fe nanoparticles in ionic liquids with strongly coordinating anions, e.g., halides, were not particularly stable to oxidation which makes a link to the present study [11]. Another published work shows that stability and catalytic activities were dependent on the nature of the ionic liquids and could be correlated with their ionicity [12].…”
Section: Introductionsupporting
confidence: 55%
“…Studies by TEM and UV-Vis spectroscopy showed that nanoparticles can be regenerated and their activity recovered by reversing sintering [10]. The same group also showed that Fe nanoparticles in ionic liquids with strongly coordinating anions, e.g., halides, were not particularly stable to oxidation which makes a link to the present study [11]. Another published work shows that stability and catalytic activities were dependent on the nature of the ionic liquids and could be correlated with their ionicity [12].…”
Section: Introductionsupporting
confidence: 55%
“…Au NPs in TAPILs in the presence of oxygen oxidize to Au( i ) and then to Au( iii ); 37 similarly, Fe NPs in alcohol or water are protected from oxidative dissolution by a thin layer of passivating FeO x on the surface, while in TAPILs, they oxidize to soluble Fe( iii )Cl x ( x −3)− species. 39 Maier and co-workers found that metallic Cu, Ag, and Au foils showed considerable mass loss after exposure to [C 6 C 1 Im][Br 2 I] for 6 h at 40 °C; XPS was used to determine the final oxidation states of the dissolved metallic species. It was determined that only the monovalent ions [Au( i ), Ag( i ), Cu( i )] were formed.…”
Section: Resultsmentioning
confidence: 99%
“…34–36 They have also shown interesting properties related to catalyst recycling vis-à-vis the regeneration of catalytically deactivated metal NPs through redox cycles. 37–39…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Au NPs in TAPILs in the presence of oxygen oxidize to Au(I) and then to Au(III); 37 similarly, Fe NPs in alcohol or water are protected from oxidative dissolution by a thin layer of passivating FeO x on the surface, while in TAPILs, they oxidize to soluble Fe(III)Cl x (x−3)− species. 39 Maier and co-workers found that metallic Cu, Ag, and Au foils showed considerable mass loss aer exposure to [C 6 C 1 Im][Br 2 I] for 6 h at 40 °C; XPS was used to determine the nal oxidation states of the dissolved metallic species. It was determined that only the monovalent ions [Au(I), Ag(I), Cu(I)] were formed.…”
Section: Temporal Changes In Cu Speciation Within the Compositesmentioning
confidence: 99%